Playing the cards you're dealt - Johnson, Varian 1977- (Scholastic Press, 2021)
"Ten-year-old Anthony Joplin has made it to double digits! Which means he's finally old enough to play in the spades tournament every Joplin Man before him seems to have won. So while Ant's friends are stressing about fifth grade homework and girls, Ant only has one thing on his mind: how he'll measure up to his father's expectations at the card table. Then Ant's best friend gets grounded, and he's forced to find another spades partner. And Shirley, the new girl in his class, isn't exactly who he has in mind. She talks a whole lot of trash- way more than his old partner. Plus, he's not sure that his father wants him playing with a girl. But she's smart and tough and pretty, and knows every card trick in the book. So Ant decides to join forces with Shirley--and keep his plans a secret. Only it turns out secrets are another Joplin Man tradition. And his father is hiding one so big it may tear their family apart... "--Dust jacket
Keywords: Junge; Kartenspiel; Sucht; African American boys / Juvenile fiction; African American families / Juvenile fiction; Spades (Game) / Juvenile fiction; Fathers and sons / Juvenile fiction; Playing cards / Juvenile fiction; Card players / Juvenile fiction; Family secrets / Juvenile fiction; Secrecy / Juvenile fiction; Preteen girls / Juvenile fiction; Friendship / Juvenile fiction; Garçons noirs américains / Romans, nouvelles, etc. pour la jeunesse; Familles noires américaines / Romans, nouvelles, etc. pour la jeunesse; Pères et fils / Romans, nouvelles, etc. pour la jeunesse; Cartes à jouer / Romans, nouvelles, etc. pour la jeunesse; Joueurs de cartes / Romans, nouvelles, etc. pour la jeunesse; Secrets de famille / Romans, nouvelles, etc. pour la jeunesse; Kinderbuch